2019
DOI: 10.1093/tas/txz029
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal dietary supplementation of cholecalciferol (vitamin D3) and 25(OH)D3 on sow and progeny performance1

Abstract: Abstract A total of 69 sows (DNA Line 200 × 400) and their progeny were used to determine if feeding a combination of vitamin D3 and 25(OH)D3 influences neonatal and sow vitamin D status, muscle fiber morphometrics at birth and weaning, and subsequent growth performance. Within 3 d of breeding, sows were allotted to one of three dietary treatments fortified with 1,500 IU/kg vitamin D3 (CON), 500 IU/kg vitamin D3 + 25 μg/kg 25(OH)D3 (DL), or 1,500 IU/kg vitamin D3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…In contrast, the results of the CON animals indicate that at least individual sows presented with 25-OHD 3 plasma concentrations below the reported reference range of 35-70 ng/mL [26]. In line with the present results, Flohr et al [8], Thayer et al [9], Weber et al [10] and Coffey et al [27] also demonstrated positive effects of replacing vitamin D 3 with 25-OHD 3 on the vitamin D status of sows.…”
Section: Vitamin D Status Plasma Minerals and Bone Metabolismsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, the results of the CON animals indicate that at least individual sows presented with 25-OHD 3 plasma concentrations below the reported reference range of 35-70 ng/mL [26]. In line with the present results, Flohr et al [8], Thayer et al [9], Weber et al [10] and Coffey et al [27] also demonstrated positive effects of replacing vitamin D 3 with 25-OHD 3 on the vitamin D status of sows.…”
Section: Vitamin D Status Plasma Minerals and Bone Metabolismsupporting
confidence: 88%
“…Despite increased plasma concentrations of 25-OHD 3 , the results of previous studies in sows and their offspring [8][9][10] that investigated the use of 25-OHD 3 instead of vitamin D 3 under conditions of adequate protein and phosphorus supply are inconsistent. However, with a dietary reduction in phosphorus, positive effects of 25-OHD 3 on the performance and digestibility of calcium (Ca) and phosphorus have already been demonstrated in growing pigs [11].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in outcomes between our study and these others may be due to the doses of vitamin D tested. For example, Thayer et al [5], investigated total vitamin D (D3 alone or combined with 25(OH)D3) levels per kg diet ranging from 1,500 IU to 3,500 IU, 1,000 IU to 2,000 IU and 800 IU to 1,600 IU for sow, nursery pigs, and growing and finishing pigs respectively and reported no effects of treatments on reproduction or pig growth performance. In the current study the total vitamin D/kg diet (basal D3 alone or basal D3 plus 2,000 IU 25(OH)D3) ranged from 2,000 IU to 4,000 IU, 2,500 IU to 4,500 IU and 1,750 IU to 3,750 IU for sows, nursery and growing and finishing pigs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The longer-term consequences on animal health remain to be established. Several studies reported that supplementation of 25(OH)D 3 resulted in increased serum 25(OH)D 3 response in sows, neonatal pigs, nursery pig, grower, and finisher pigs [ 4 , 5 , 7 , 38 40 ]. In the present study, an increase in serum 25(OH)D 3 and Ca concentration was detected in growing pigs that received diets supplemented with 50 μg/kg 25(OH)D 3 post weaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation